Adapting and Going the Extra Mile: A Qualitative Study of Palliative Care in Rural Northern Norway From the Perspective of Healthcare Providers - Ervik, Bente; Brøndbo, Birgit; Johansen, May-Lill (Cancer Nursing, 2020)
Background - Despite significant developments in palliative care in recent decades, we still find important differences in access to and delivery of care in rural Norway. Objective - The aim of this study was to explore what healthcare professionals consider necessary to provide equality in care for palliative patients in rural areas. Methods - A qualitative approach with focus group discussions and individual interviews with 52 health professionals was used, starting with 5 uniprofessional focus groups of general practitioners and nurses/cancer nurses, followed by 5 interprofessional groups and 6 individual interviews. Interview transcripts were analyzed thematically. Results - We found local variations in organization, competence and access to palliative care, and challenging geographical conditions. It was essential to be proactive, flexible and willing to go the extra mile, but this may conceal the need for a stronger focus on competence and organization of palliative care. Access to written guidelines and practical tools was important, as was forming palliative teams for particular situations. Conclusions - Palliative care needs strengthening in rural areas, and increased competence for all healthcare professionals is vital to increase equality in care. Geographical conditions require locally adapted solutions. Access to guidelines and interprofessional collaboration are essential.